CORELATION OF ALLERGIC RHINITIS AND HYPOTHYROIDISM IN PATIENTS IN A RURAL TERTIARY CARE HOSPITAL-A CROSS SECTIONAL STUDY - R Abhirami Krishnan; Kiran M Naik; Aswathy M P; Ragavendra A R (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Introduction: Allergic rhinitis (AR) and hypothyroidism are common conditions with potential interrelated pathophysiological mechanisms. AR is characterized by mucosal inflammation leading to symptoms such as nasal congestion, sneezing, and rhinorrhea, while hypothyroidism results from reduced thyroid hormone levels affecting various organ systems. The association between AR and hypothyroidism remains unclear, and this study aims to evaluate their correlation in a rural tertiary care hospital. Objective: The study aims to estimate the prevalence of nasal symptomatology in hypothyroid patients and assess the severity of AR in relation to thyroid hormone levels. Materials and Methods: A prospective descriptive cross-sectional study was conducted on 100 hypothyroid patients presenting with AR symptoms at a tertiary care centre. Patients underwent thyroid function tests (TSH, T3, T4) and nasal examinations using the NOSE questionnaire. Data were analyzed using statistical methods, including chi-square and correlation tests, to assess the association between AR severity and thyroid dysfunction. Results: The study found a significant prevalence of nasal symptoms among hypothyroid patients, with sneezing (88%), nasal congestion (84%), and nasal obstruction (85%) being the most common. TSH levels were significantly higher in patients with severe AR (p = 0.0072), while T3 and T4 variations were less pronounced. The NOSE scores showed improvement over three months, indicating effective symptom management despite stable thyroid hormone levels. Conclusion: There is a significant association between AR severity and hypothyroid status, particularly in relation to TSH levels. Evaluating thyroid function in AR patients may aid in better management and treatment strategies.